Filmowe reprezentacje ostatniej wieczerzy jako locus theologicus (trzy wizje biblijnej sceny) - Kolasińska-Pasterczyk, Iwona (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The cinematic scenes of the Last Supper were treated as a challenge to visual theology. As the Last Supper, which in the films about Jesus of Nazareth (and, of course, the gospels) is the culmination (and also a turning point as an event ending Jesus` earthly activity), it is possible to see the essence of the theological message of films referring to the gospel in its presentation. The scenes of the Last Supper from three films were subjected to a comparative analysis, each of which is an individual director`s vision. These are The King of Kings (1961) by Nicholas Ray, The Passion of the Christ (2004) by Mel Gibson and The Thorn of God (2015) by Óscar Parra de Carrizosa. The selection criterion was the importance given in the films to the scenes of the Last Supper and their mutually diverse representations. It has been shown how the established new transmission of visual theology modifies the meanings determined by classical theology, basically not deviating from the framework set by it.